The Calgary student run clinic in context: a mixed-methods case study - Danielle Maria Smith (Canadian Medical Education Journal, 2019)
Background: Student Run Clinics (SRCs) provide students with clinical education while caring for underserved populations. While much of the research on SRCs comes from the USA, SRCs in other contexts need to be appraised in the context of the systems they interact with. This study explored how stakeholders in the University of Calgary’s SRC perceived its purpose and beneficiaries with respect to patients, students, undergraduate medical education, and its intersections within the healthcare system in Calgary.